Dynamic Governance in Population Services Under the “Dukcapil in the Village” Program in Batu Bara Regency - Muhammad Azhari Ihsan; Jona Bungaran Basuki Sinaga; Lilis Sholihah (CV SCRIPTA INTELEKTUAL MANDIRI, 2026)
Population administration services play a crucial role in ensuring legal identity, social inclusion, and access to public services. This study examines the implementation of dynamic governance in population administration services through the Dukcapil in the Village Program in Batu Bara Regency. The research employed a qualitative approach within a post positivist paradigm. Data were collected through in depth interviews, observation, and document analysis involving officials of the Population and Civil Registration Office, village service personnel, and community members. Data analysis was conducted using ATLAS.ti based on the dynamic governance framework developed by Neo and Chen. The findings indicate that governance capabilities have contributed to improving service accessibility and administrative responsiveness through service decentralization and technology utilization. Institutional culture has supported transparency, professionalism, and citizen oriented service values, although public trust and community participation remain uneven across villages. Organizational change has encouraged workforce adaptation, digital transformation, and service innovation, yet several constraints persist, including limited human resources, infrastructure disparities, and low levels of digital literacy. The study concludes that sustainable population service improvement requires the integration of adaptive governance capacity, strong institutional values, and continuous organizational transformation to ensure inclusive, responsive, and citizen centered public services.